Clinical Effect of Open-wedge High Tibial Osteotomy in Treatment of Kellgren-lawrence IV Knee Osteoarthritis Associated with Varus Tibial Deformity. Issue 9 (28th September 2020) - Sha, Yu; Yan, Lei
Objectives: The purpose of this study is to evaluate the clinical efficacy of open-wedge high tibial osteotomy (HTO) in treatment of kellgren- lawrence IV anterior medial knee osteoarthritis with varus tibia. Methods: Between 2016 and 2018, 56 patients with kellgren -lawrence IV knee osteoarthritis associated with varus tibial deformity who underwent a medial open-wedge high tibial osteotomy at a tertiary hospital were prospectively followed up. The surgical effect and postoperative complications were observed and analyzed. Meanwhile, the hospital for special surgery (HSS) scores of knee function before operation and at the last follow-up after operation was compared. Results: The median follow up was 19.8 months (range, 18 to 24 months). At the last follow-up, there was 40 excellent cases, 14 good cases, 2 fair case and 0 poor case. There were no complications such as vascular and nerve injury, internal fixation fracture and infection. The HSS score of knee function (89.6±3.9) at the last follow-up after operation was higher than (63.2±6.4) points before operation, and the difference was statistically significant ( P ＜0.05). Conclusion: Medial opening high tibial osteotomy shows remarkable therapeutic effect for patients with knee osteoarthritis associated with varus tibial deformity, and it can effectively relief the pain of knee joint with less postoperative complications.